Evaluation of the Antifungal Activity of Clove and Cinnamon Essential Oils against Candida Albicans - Ismail, H. Y.; Mustapha, A.; Ngoshe, I. Y.; Musa Ibn Abbas; Adamu, A.; Shettima, A. L.; Dan-Iya, S. A. (UMYU Journal of Microbiology Research)
Study’s Excerpt: